Asset management corporation of Nigeria – a pretentious special purpose vehicle (2015)
In contemporary financial world, business organisation most especially financially distressed companies and companies with low or mid-tier credit ratings have securitised different types of assets (loans, credit cards, auto receivables, intellectual property, etc.) through the use of SPVs .The enactment of the AMCON ACT 2010 was specifically to bail out the Nigerian banks by buying and taking over the 'toxic' assets that were threatening to destroy the banks and the economy. This paper analysed the essential features of the procedure for securitisation and asset management modules as a background to critically examine the AMCON ACT and whether the Asset Management Corporation is an SPV or not. The paper concludes that AMCON is not an SPV but a special statutory creation to solve a special problem confronting the banks and the economy.